COMMUNICATION PATTERN OF LEADERS WITH EMPLOYEES IN YAYASAN PENYANDANG CACAT MANDIRI YOGYAKARTA (Descriptive Study of Communication Pattern on Leaders and Employees Organization Management of Yayasan Penyandang Cacat Mandiri Yogyakarta) - Reni Krisnawati; Siti Fatonah; Senja Yustitia (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2018)
Difable conditions in Indonesia is currently quite apprehensive. Lack of attention from the government and the community impacts on the lack of opportunities obtained in work, this condition makes the level of living welfare of the disabled is still low. One of the foundations that provide disabled opportunities for work is the Foundation for Persons with Disabilities / YPCM, an organization that accommodates the disabled / disabled handicap to work to make wooden handicrafts. The majority of the employees in the foundation are disabled and led by a chairman of a non-disabled foundation. The purpose of this study is to know the pattern of organizational communication between leaders and employees in the management of YPCM, as well as to know the obstacles in the pattern of organizational communication at YPCM. This research uses Fielder Contigency Theory with qualitative descriptive research method. The result of the research shows that the communication pattern of the leadership organization and the employees in the management of Yayasan Penyadang Cacat Mandiri Yogyakarta forms a unidirectional communication pattern, wheel communication, two-way communication pattern and there is communication pattern in media usage. In addition, the obstacles that occur are influenced by several factors, namely the low communication intensity between leaders and employees at YPCM, as well as the role of the Foundation Chairman who is lacking in becoming a master in the foundation of things that influence the communication between leaders and employees at YPCM. The pattern of communication made more placed Head of Production that plays an important role in the activities of the organization due to the lack of function of the Chairman of the Foundation as a leader in YPCM.